Implementation Of Tourism Implementation Through The Development Of Tourism Villages In Fostering Independence And Empowerment Of The Creative Economy - Tahlia Kartika; Anisa Riani; Sri Wulandari; Dedet Erawati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research aims to explore the implementation of tourism implementation through the development of tourism villages in fostering independence and empowerment of the creative economy. This study uses a qualitative approach carried out by taking information from successful tourism village communities in Cirebon Regency. Data were collected through in-depth interviews, participatory observations, and document analysis. The results of the study show that the development of tourism villages significantly contributes to the economic independence of local communities through skill improvement, job creation, and strengthening social networks. In addition, the empowerment of the creative economy in tourism villages encourages local product innovation and increases market competitiveness. This implementation is supported by the government, the community, and the private sector, as well as environmental sustainability as the main supporting factor. In conclusion, the development of tourism villages not only increases economic independence, but also strengthens a sustainable creative economy at the local level.